Cord Blood Platelet Rich Plasma Derivatives for Clinical Applications in Non-transfusion Medicine - Samarkanova, Dinara; Cox, Steven; Hernandez, Diana; Rodriguez, Luciano; Casaroli-Marano, Ricardo P.; Madrigal, Alejandro; Querol, Sergio (Frontiers in Immunology, 2020)
Cord blood plasma (CBP) has been investigated as a potential therapeutic agent for the treatment of diverse conditions including ocular surface disease and skin ulcers. We have developed processes for the formulation of several cord blood plasma preparations, which have different composition and attributes. Here we describe the molecular characteristics of these preparations and we make recommendations as to their most appropriate clinical application based on functional and immunomodulatory profiles. We show that incubation of adult peripheral blood mononuclear cells (PBMCs) with all three preparations dramatically reduced the production of INFgamma and the expression of NKG2D and CD107a in NK, NKT and T cells thus diminishing their activation, we propose that the likely mechanism is the high levels of soluble NKG2D ligands present in plasma. Of the three preparations we investigated, CB-platelet lysate (PL) and platelet releaseate (PR) have higher concentrations of trophic and pro-angiogenic factors CB- platelet poor plasma (PPP) has the lowest concentration of all analytes measured. Based on these finding we propose that CB-PR is the most suitable raw material for skin wound patches, while CB-PL and PPP can be used to prepare eye drops for severe ocular surface pathologies and inflammatory conditions such as corneal ulcers or sever dry eye disease (DED) respectively